The Macroeconomic Effects of Capital Controls and the Stabilization of the Balance of Trade - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 1990)
A dynamic stochastic equilibrium model of a small open economy is used to quantify the macroeconomic effects of introducing capital controls to stabilize the balance of trade. This model focuses on the role of international trade and foreign debt as instruments that help smooth consumption in response to productivity or terms-of-trade disturbances. The model rationalizes some key empirical regularities that characterize business fluctuations and the dynamics of savings and investment in post-war Canada. The results show that capital controls have small effects on both the basic characteristics of macroeconomic fluctuations and the level of welfare. A fiscal strategy that successfully enforces capital controls by introducing taxes on foreign interest income is also studied in some detail.